Spatiotemporal dynamic relationships and simulation of urban spatial form changes and land surface temperature: a case study in Chengdu, China - Jian, Ling; Xia, Xiaojiang; Wang, Yuanqiao; Liu, Xiuying; Zhang, Yue; Yang, Qianchuan (Frontiers in Public Health, 2024)
Exploring the spatiotemporal dynamic evolution of local climate zones (LCZs) associated with changes in land surface temperature (LST) can help urban planners deeply understand urban climate issues. The evolution of 3D urban spatial form at the regional scale in Chengdu from 2010 to 2020 was monitored, and their changes in relation to LST were analyzed. The spatiotemporal patterns of LST were examined by the integration of the Space-Time Cube model and emerging hot spot analysis. The ordinary least squares model was used to fit the dynamic relationship (DR) between the changes in urban spatial patterns and changes in LST and to reveal the changes of urban spatial patterns that are closely related to the rise in LST. Finally, a prediction model based on curve fitting and random forest was integrated to simulate the LST of Chengdu in 2025. Results show the following: (1) The evolution of the urban spatial form consists of three stages: initial incremental expansion, midterm incremental expansion and stock renewal, and late stock renewal and ecological transformation. (2) The overall LST shows a warming trend, and the seven identified LST spatiotemporal patterns are dominated by oscillating and new hot spots patterns, accounting for 51.99% and 11.44% of the study area, respectively.(3) The influence of the built environment on the rise of LST is greater than that of the natural environment, and the building density has a greater effect than the building height. (4) The DR between change in urban spatial pattern and LST differs in different built environments and time periods, and is negatively correlated with the natural environment. (5) The thermal environment of the city will warm up as a whole in the future, and the area affected by the heat island will shift to the central of the city.